2022
DOI: 10.1007/s00590-022-03206-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival, functional outcome and satisfaction of first revision total knee arthroplasty at a mean eleven-year follow-up

Abstract: Purpose Providing long-term outcome data after rTKA and compare one- versus two-stage and septic versus aseptic revisions. Methods This study represents a single-center retrospective study of first rTKAs performed for any reason with a final follow-up of a minimum of five years. Outcome parameters included stability assessment ROM, radiologic assessment, HSS score, KSS score, OKS score, EQ-5D-3L and VAS. 44 patients were included in the study. Subgroups an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous studies have reported conflicting results regarding the clinical outcomes after septic and aseptic revision TKAs. Hecker et al reported no significant differences in the Hospital for Special Surgery (HSS) knee score, Oxford Knee Score, Knee Society Score (KSS) subscores, and EuroQol-5 Dimensions (EQ-5D) visual analog scale (VAS) score and index between septic and aseptic revision TKAs 31 . In contrast, Ro et al reported poorer clinical outcomes (range of motion, KSKS, and HSS score) for septic revision TKAs (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported conflicting results regarding the clinical outcomes after septic and aseptic revision TKAs. Hecker et al reported no significant differences in the Hospital for Special Surgery (HSS) knee score, Oxford Knee Score, Knee Society Score (KSS) subscores, and EuroQol-5 Dimensions (EQ-5D) visual analog scale (VAS) score and index between septic and aseptic revision TKAs 31 . In contrast, Ro et al reported poorer clinical outcomes (range of motion, KSKS, and HSS score) for septic revision TKAs (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the available literature. [4,8,25] The reason for using such implants in primary cases is the complex nature of these cases including severe bone loss, high grade deformities, ligamentous and muscular insufficiency associated with an increased risk of a less favorable outcome [21]. Another proposed indication is a intraarticular fracture in the elderly patient [19].…”
Section: Discussionmentioning
confidence: 99%
“…[21] Even current generation RHKs such as the one used in this cohort were shown to be associated with high revision rates of 10-20% during the first 2 years when used in revision and complex primary cases. [7,8,22,23] There is an ongoing debate on, whether RHK should be used in complex primary cases. [9] Recent studies showed acceptable survival rates of 80-90% after Abbreviations: ASA American society of anesthesiologists, BMI body mass index, TKA total knee arthroplasty, RHK rotating hinge knee, ROM range of motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation